STATE’S COUNTER-NARRATIVES ON TERRORISM CAMPAIGN AS COUNTER-TERRORISM STRATEGY: INDONESIA’S PERSPECTIVE - Mulyono, Imam Edy; Gustarina, Fauzia (Universitas Djuanda, 2022)
Terrorism has become a grave threat to countries around the world. Claims that the action is a movement in the name of religion are part of a campaign carried out by terrorists. This terrorism campaign aims to create a support base from the religious community. The purpose of this study is to examine the Government's efforts to respond to acts of terrorism, to find out the speed at which terrorists carry out campaigns, and how the Government indirectly plays an essential role in the process of campaigning for terrorism through statements issued in response to various acts of terror that have occurred in Indonesia. This research method uses a qualitative approach with data collection techniques through library research—data analysis using content analysis. The results of the study show that acts of terrorism are radical religious acts, tend to make terrorist campaigns spread faster, and are more effective in creating a base of support. It proves that the choice of government policy in Counter-narratives on Terrorism can determine whether the terrorist campaign is stopped or even more deployed. The research results recommend a more practical concept proposal for the Indonesian Government's Counter-Terrorism Narrative policy in dealing with terrorism campaigns as part of Indonesia's Counter-Terrorism strategy.